2010
DOI: 10.1093/ndt/gfq001
|View full text |Cite
|
Sign up to set email alerts
|

Daily peritoneal ultrafiltration predicts patient and technique survival in anuric peritoneal dialysis patients

Abstract: The present study demonstrates a strong predictive value of daily peritoneal UF for both technique and patient survival in prevalent anuric PD patients. Identifying markers of satisfactory fluid status, as well as optimizing therapy to meet UF goals, remains an important clinical target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
3
20
0
2
Order By: Relevance
“…They conducted a retrospective study in 150 anuric CAPD patients with a mean follow-up of 57.7 months after anuria and showed that D/P Cr was a strong independent predictor for mortality, but the results regarding the UF volume of patients was unclear. Similar results were shown in another retrospective study that included 86 Chinese anuric CAPD patients with a median follow-up of 25.3 months, such that although D/P Cr was not associated with mortality after adjustment for confounders, the mortality risk was significantly reduced when baseline UF was increased above 1 l/24 h [12] . Furthermore, the EAPOS study, which was a 2-year prospective multicenter study consisting of 177 anuric patients treated with APD, suggested that peritoneal solute transport status at baseline did not influence patient, technique or combined patient and technique survival, whereas baseline UF below the 750 ml/24 h was associated with poor survival [4] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…They conducted a retrospective study in 150 anuric CAPD patients with a mean follow-up of 57.7 months after anuria and showed that D/P Cr was a strong independent predictor for mortality, but the results regarding the UF volume of patients was unclear. Similar results were shown in another retrospective study that included 86 Chinese anuric CAPD patients with a median follow-up of 25.3 months, such that although D/P Cr was not associated with mortality after adjustment for confounders, the mortality risk was significantly reduced when baseline UF was increased above 1 l/24 h [12] . Furthermore, the EAPOS study, which was a 2-year prospective multicenter study consisting of 177 anuric patients treated with APD, suggested that peritoneal solute transport status at baseline did not influence patient, technique or combined patient and technique survival, whereas baseline UF below the 750 ml/24 h was associated with poor survival [4] .…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the association between peritoneal membrane status and mortality in anuric patients who are on PD has been poorly investigated. One analysis for 86 anuric continuous ambulatory peritoneal dialysis (CAPD) patients demonstrated that each 0.1 increment of dialysate to plasma creatinine ratio (D/P Cr) was not associated with either patient survival or technique survival [12] . In contrast, a study from Hong Kong reported that higher D/P Cr level (RR = 1.505 for every 0.1 increase, 95% CI 1.202-1.885, p value = 0.000) was associated with an increased risk of all-cause mortality in anuric CAPD patients [13] .…”
Section: Introductionmentioning
confidence: 99%
“…As accumulating evidence has found that fluid status strongly influences the clinical outcome of dialysis patients [17,18,19,20], we believe that patients who have too much interdialytic weight gain are not suitable for twice-weekly HD even when a very high spKt/V could be ensured, and for these patients, a timely switch from twice-weekly HD to thrice-weekly HD may be important.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] But there are no clear-cut criteria for the diagnosis of hypovolemia or hypervolemia. Some patients have elevated systolic blood pressure, despite being euvolemic which is thought to be due to vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…For both the treatment modalities, international guidelines underline volume status for dialysis adequacy. 1 One of the main factors determining the morbidity and mortality in PD patients is volume status [2][3][4][5][6][7] and may even be more important than solute clearance. 8 Besides clinical findings (blood pressure, presence of edema, and weight gain), echocardiography, Dual Energy X-ray Absorptiometry (DEXA), direct measurement of extracellular and total body water (TBW), brain natriuretic peptide (BNP) has been used for the determination of hydration status.…”
Section: Introductionmentioning
confidence: 99%